Sukces szkolny i jego rodzaje. Obiektywny i subiektywny wymiar sukcesu szkolnego - Nikel, Łukasz; Pacholczyk, Weronika; Żołądkowska, Sandra; Dziergwa, Oliwia (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The aim of the article is to present various definitions, theories, and indicators of a student`s academic success. It explains what school success entails, its types, objective and subjective dimensions, and determinants. The definitions and theories presented indicate that school success is a complex concept that can be viewed from multiple perspectives and lacks a clear-cut definition. It encompasses achieving educational goals, school involvement, satisfaction with learning, acquiring knowledge and skills, perseverance, and the student`s personal, social, and moral development.
Keywords: szkoła; uczeń; sukces szkolny; wymiar obiektywny; wymiar subiektywny; school; students; school success; objective dimensions; subjective dimensions